Determinants of Verification Performance: The Role of Structure and Resilience in Indonesia's Oil & Gas Domestic Content Compliance - Supriyatno; Nancy Yusnita; Yayan Hadiyat (International Journal Administration, Business & Organization, 2026)
The purpose of this study is to formulate strategies for enhancing employee performance at Oil and Gas Industry in Indonesia regarding the fulfillment of Domestic Content Requirements (Tingkat Komponen Dalam Negeri or TKDN) through the optimization of the TKDN verification process. Achieving performance targets in TKDN verification is a critical objective for Oil and Gas Industry as part of its compliance with applicable regulations. This study examines the influence of Organizational Structure and Adversity Quotient on Employee Performance, with Work Motivation serving as an intervening variable. A quantitative approach was employed using a survey of 80 respondents, with data analyzed using Descriptive Statistics and Structural Equation Modeling (SEM). The results demonstrate that both Organizational Structure and Adversity Quotient have a significant direct positive effect on Employee Performance, and both significantly influence Work Motivation. However, Work Motivation does not have a significant effect on Employee Performance, indicating that the mediating role of Work Motivation is not supported. These findings suggest that strengthening TKDN verification performance is more effectively achieved by optimizing organizational mechanisms through the implementation of effective work procedures and supervision/coordination as well as by enhancing individual resilience during the verification process. Such measures are essential to ensuring that this Oil and Gas Industry meets its TKDN achievement targets and remains compliant with prevailing regulations.